Safety and tolerability of a novel monoclonal antibody cocktail for rabies post-exposure prophylaxis - Nidhi Fotedar; Haradanahalli Shankaraiah Ravish (npj Vaccines)
Abstract Rabies is one of the most lethal viral zoonoses, particularly in low- and middle-income countries where access to post-exposure prophylaxis is limited. Conventional post-exposure prophylaxis relies on rabies immune globulin and vaccination. This study evaluated the safety of a monoclonal antibody cocktail, docaravimab and miromavimab, in 159 patients with severe animal bites. The cocktail was administered locally to 94.3 percent of participants and both locally and systemically to 5.7 percent. Adverse events were reported in 10.7 percent of cases, predominantly mild and local, with no systemic or severe reactions observed. No cases of rabies occurred during six months of follow-up. These findings suggest that the monoclonal antibody cocktail has a favorable safety profile, potentially serving as a viable alternative to traditional rabies immune globulin in post-exposure prophylaxis.